Developing dynamic capabilities to survive a crisis: Tourism organizations' responses to continued turbulence in Libya. (11th April 2019) - Mansour, Hafez E.L.; Holmes, Kirsten; Butler, Bella; Ananthram, Subramaniam
Abstract: This paper identifies specific types of dynamic capabilities that enable tourism firms to survive the crisis caused by the Libyan civil war. The literature on dynamic capabilities has matured, but little is known about the specific types of dynamic capabilities that enable firms to survive turbulent conditions. Using case studies of eight Libyan tourism firms, we find that ongoing interactions between firms and their environments and the specific actions taken by managers and employees are crucial to firms' survival and adaptation to the new environment. Our paper makes a theoretical contribution to the dynamic capabilities and crisis management literature.